"But Girls Can Do that Too": Discussing Gender Equality with Children in a Progressive Jewish Context. Issue 3 (2nd July 2020) - Jackson-Gordon, Rachel
ABSTRACT: This study is a qualitative project which took place with six elementary-aged children in a progressive Jewish education program. The children took photos around their synagogue of items related to gender. The children chose their favorite photos, then explained and discussed the photos with their peers. All explanations and discussions were recorded, transcribed verbatim, and inductively analyzed. Results emphasize the importance of providing opportunities for children to voice their opinions on social-justice related constructs like gender equality. The results also speak to the role of institutions such as synagogues as environments where children develop their beliefs about gender.